Evaluation of the Structural Model of Madrasah Teacher Training Transfer in Online Training - Siswanto, Yudi; Shofwan, Imam; Prilianti, Ratna (Universitas Negeri Semarang, 2025)
This study aims to evaluate the structural model of madrasah teacher training transfer in online training, focusing on the influence of self-efficacy, training design, and work environment on teaching skill transfer. This study uses a quantitative approach through a survey of 171 madrasah teachers in Central Java and D.I. Yogyakarta who participated in e-training from the Semarang Religious Education and Training Center (BDK). The instruments used were questionnaires based on self-efficacy scales, training design, work climate, and training transfer, and data were analyzed using Structural Equation Modeling (SEM) with the help of AMOS 24. The results of the analysis showed that the three variables (β = 0.33, p < 0.001), training design (β = 0.36, p < 0.001), and work environment (β = 0.24, p < 0.001) had a positive and significant effect on training transfer. The model explains the 55% variance in teaching skill transfer. The transfer of teaching skills in online training is significantly influenced by the individual characteristics of the teacher, the quality of the training design, and the support of the work environment. These three factors need to be considered in an integrated manner to increase the effectiveness of teacher training. The results of the study provide important recommendations for training organizers to pay more attention to the internal aspects of participants (self-efficacy), design applicable and relevant training, and create a work environment that supports the implementation of training results. The study contributes an up-to-date empirical understanding of the key factors influencing the transfer of madrasah teacher training in the digital age and highlights the importance of integration between personal, design, and work context factors in teacher professional development through online training.